Routledge Handbook of Environmental Displacement and Migration
1 online resource (472 pages)
Keywords: "The last twenty years have seen a rapid increase in scholarly activity and publications dedicated to environmental migration and displacement, and the field has now reached a point in terms of profile, complexity, and sheer volume of reporting that a general review and assessment of existing knowledge and future research priorities is warranted. So far, such a product does not exist. The Routledge Handbook of Environmental Displacement and Migration provides a state-of-the-science review of research on how environmental variability and change influence current and future global migration patterns and, in some instances, trigger large-scale population displacements. Drawing together contributions from leading researchers in the field, this compendium will become a go-to guide for established and newly interested scholars, for government and policymaking entities, and for students and their instructors. It explains theoretical, conceptual, and empirical developments that have been made in recent years; describes their origins and connections to broader topics including migration research, development studies, and international public policy and law; and highlights emerging areas where new and/or additional research and reflection are warranted.The structure and the nature of the book allow the reader to quickly find a concise review relevant to conducting research or developing policy on particular topics, and to obtain a broad, reliable survey of what is presently known about the subject."--Provided by publisher.